Intestinal mononuclear cells primed by systemic interleukin-12 display long-term ability to aggravate colitis in mice - Pedrotti, Luciano Pablo (2016)
To address whether the burst of systemic interleukin-12 (IL-12) influences intestinal inflammation elicited by luminal stimuli, we induced IL-12 release by cDNA injection in C57BL/6 mice and simultaneously started dextran sulphate sodium administration. The sequence of the inflammatory response triggered by IL-12 release was characterized by assessing myeloperoxidase activity and histological damage in colon samples on days 1, 3, 5 and 7 after colitis induction. To evaluate the persistence of IL-12 priming, colitis was induced in mice 7 or 60 days after cDNA injection. Under IL-12 influence, the development of acute colitis presented a faster and selective infiltration of inflammatory mononuclear cells in the lamina propria. Recruitment was driven by systemic cytokines rather than luminal antigens. Interestingly, when colitis was triggered 7 or 60 days after the cytokine storm, cells maintained the ability to worsen clinical signs of intestinal inflammation. Together, a systemic IL-12 burst effectively primed intestinal cells that became more prone to develop inflammatory responses. Activation was long-lasting because intestinal cells maintained their inflammatory potential and their ability to aggravate colitis.